2018
DOI: 10.1007/978-3-030-00928-1_54
|View full text |Cite
|
Sign up to set email alerts
|

A Lifelong Learning Approach to Brain MR Segmentation Across Scanners and Protocols

Abstract: Convolutional neural networks (CNNs) have shown promising results on several segmentation tasks in magnetic resonance (MR) images. However, the accuracy of CNNs may degrade severely when segmenting images acquired with different scanners and/or protocols as compared to the training data, thus limiting their practical utility. We address this shortcoming in a lifelong multi-domain learning setting by treating images acquired with different scanners or protocols as samples from different, but related domains. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(109 citation statements)
references
References 24 publications
(38 reference statements)
1
100
0
Order By: Relevance
“…Existing successful practice using deep networks is to train and test the models with the same data source. However, it has been frequently revealed in very recent works, that the models would perform poorly on unseen datasets [7], [10], [43]. Resolving the domain adaptation issue holds great potentials for, applying trained deep learning models to wider clinical use, building more powerful networks using largescale database combing images from multiple sites, and helping to understand how the networks capture the data distributions to make recognition predictions.…”
Section: Discussionmentioning
confidence: 99%
“…Existing successful practice using deep networks is to train and test the models with the same data source. However, it has been frequently revealed in very recent works, that the models would perform poorly on unseen datasets [7], [10], [43]. Resolving the domain adaptation issue holds great potentials for, applying trained deep learning models to wider clinical use, building more powerful networks using largescale database combing images from multiple sites, and helping to understand how the networks capture the data distributions to make recognition predictions.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, it also restricted the adaptation capacity to the new domain. Karani et al suggested that learning batch normalization parameters for each scanner and sharing the convolutional filters between all scanners addressed the distribution shift among scanners [91]. The experiment showed this strategy can be adapted to new scanners or protocols with only a few (≈ 4) labelled images and without degrading performance on the previous scanners.…”
Section: Choosing and Training Modelsmentioning
confidence: 99%
“…Despite the powerful local and global context that CNNs generally provide, they are more vulnerable to subtle contrast differences between training and test MRI images than model-based and MALF-based methods. A recent work by Karani et al (2018) describes a brain segmentation CNN trained to consistently segment multi-scanner and multi-protocol data. This framework adds a new set of batch normalization parameters in the network as it encounters training data from a new acquisition protocol.…”
Section: Prior Workmentioning
confidence: 99%